Glutathione deficiency in cardiac patients is related to the functional status and structural cardiac abnormalities. - Thibaud Damy (PLoS ONE, 2009)
BACKGROUND: The tripeptide glutathione (L-gamma-glutamyl-cysteinyl-glycine) is essential to cell survival, and deficiency in cardiac and systemic glutathione relates to heart failure progression and cardiac remodelling in animal models. Accordingly, we investigated cardiac and blood glutathione levels in patients of different functional classes and with different structural heart diseases. METHODS: Glutathione was measured using standard enzymatic recycling method in venous blood samples obtained from 91 individuals, including 15 healthy volunteers and 76 patients of New York Heart Association (NYHA) functional class I to IV, undergoing cardiac surgery for coronary artery disease, aortic stenosis or terminal cardiomyopathy. Glutathione was also quantified in right atrial appendages obtained at the time of surgery. RESULTS: In atrial tissue, glutathione was severely depleted (-58%) in NYHA class IV patients compared to NYHA class I patients (P = 0.002). In patients with coronary artery disease, this depletion was related to the severity of left ventricular dysfunction (P = 0.006). Compared to healthy controls, blood glutathione was decreased by 21% in NYHA class I patients with structural cardiac disease (P<0.01), and by 40% in symptomatic patients of NYHA class II to IV (P<0.0001). According to the functional NYHA class, significant depletion in blood glutathione occurred before detectable elevation in blood sTNFR1, a marker of symptomatic heart failure severity, as shown by the exponential relationship between these two parameters in the whole cohort of patients (r = 0.88). CONCLUSIONS: This study provides evidence that cardiac and systemic glutathione deficiency is related to the functional status and structural cardiac abnormalities of patients with cardiac diseases. These data also suggest that blood glutathione test may be an interesting new biomarker to detect asymptomatic patients with structural cardiac abnormalities.